Imitation On The Jaranan Buto Banyuwangi Musical Presentation Structure (Jurnal Seni Musik, 2021)
Jaranan Buto is one of the arts that live in Banyuwangi in addition to other arts. As a performing art, in every presentation Jaranan Buto uses accompanying music. At the beginning of its creation, the musical accompaniment of Jaranan Buto consisted of several instruments and pieces. Over time, the musical accompaniment of Jaranan Buto has experienced developments so as to form a structure for presenting the musical accompaniment of Jaranan Buto which is now commonly used. This study discusses the structure of the musical accompaniment of Jaranan Buto and its various imitations. This study used a descriptive qualitative approach by interviewing Setro Asnawi (80 years) as the creator of Jaranan Buto and Mariyono (55 years) as the second generation of Jaranan Buto Sekar Diyu dancers who were still active until this research was written. Analysis of research data starts from domain analysis, observation focused on the accompaniment of Jaranan Buto from the beginning of the stage, trance to exiting the stage, taxonomic analysis, selected observations to the final stage, namely component analysis. From these results it can be concluded that the elements of musical imitation in the accompaniment of Jaranan Buto consist of imitation of musical instruments and imitation of pieces performed from other arts.